Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Sedimentary characteristics and palaeo-ocean environment evolution of the Hejiazhai Formation in the early Tonian Period, Western Henan - Boyang Xu; Deshun Zheng; Qianqian Li; Sha Ren; Fengbo Sun; Jiaqi Fu; Xin Wang; Wentong Yang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Recent advances in spinel nickel cobalt oxide-based nanostructures for oxygen electrocatalysis - He Li; Sha Qiao; Kai Fu; Liang Zhang; Jun Wang (Fuel, 2026)

Fermentation optimization and characterization of extracellular protein-associated antifungal components from Bacillus velezensis SY01 against Cytospora pyri - Shuaishuai Sha; Lingkai Xu; Canpeng Fu; Qiuyan Han; Jiaqi Ding; Beibei Feng; Yan Zhang; Sabinur Nurmemet; Pan Xie (Physiological and Molecular Plant Pathology, 2026)

A ceRNA axis of lncRNA MSTRG.14394.1/miR-144-3p/NR1H3 responds to diverse bacterial PAMPs in teleost fish - Yishuai Li; Mengyang Chang; Suxu Tan; Wenwen Wang; Kunpeng Shi; Shaoqing Zang; Yiming Hu; Qingyang Fu; Songlin Chen; Zhenxia Sha (Fish & Shellfish Immunology, 2026)

Molecular structure controls sunlight-driven photodegradation and persistence of trace organic contaminants in surface waters - Ruiying Song; Yifu Fu; Zonghao Luo; Sha Zhu; Jiadan Xue; Richard Spinney; René M. Williams; Ruiyang Xiao (Journal of Hazardous Materials, 2026)

Genome-wide insights into the regulatory networks of ZmHsf28 in salt and drought stress - Lijun Liu; Xia Zheng; Xiaoyu Sha; Shuaibing Tian; Ziyi Luo; Yuhan Zhang; Guocheng Wei; Yuxin Li; Jingye Fu; Qiang Wang (Plant Science, 2026)

Enzyme mimics catalytic process in organic pollutants treatment: Applications, mechanisms, and challenges - Ting Peng; Sha Long; Enxu Liu; Xuran Liu; Dongbo Wang; Yukui Fu; Jin Huang (Chemical Engineering Journal, 2026)

Volcanic rock-confined core-shell nanoreactors as a highly effective and recyclable peroxymonosulfate activator for levofloxacin degradation: Performance, mechanism, and ecotoxicity assessment - Xinxi Fu; Xiangyu Li; Yang Zhong; Shuai Shao; Yonghua Chen; Sha Xie (Environmental Research, 2026)

Synergistic defect and morphology engineering of Mn-doped ZIF-8 for superior ciprofloxacin capture - Jiahao Huang; Xinxi Fu; Xinlu Zhang; Xiao Fu; Qian Liu; Sha Xie (Chemical Engineering Journal, 2026)

A Multi-omics Atlas of Gonadal Sex Differences and Characterization of the dmrt1 Gene in Gymnocypris Eckloni Herzenstein - Luo Lei; Yinhua Zhou; Qing Liu; Hejiao Li; Wuga Sha; Chaoyang Li; Suxing Fu; Yuting Duan; Rongrong Liao; Can Liu; Dapeng Gu; Linzhen Li; et al. (Marine Biotechnology, 2026)

The transcription factor OsERF74 positively regulates drought resistance by modulating abscisic acid catabolism in rice - Ziyi Luo; Chen Tang; Liping Wang; Xiaoyu Sha; Yuhan Zhang; Wenjiang Liu; Jingye Fu; Qiang Wang (Journal of Plant Physiology, 2026)

Near-unity quantum yield blue hybrid cuprous halide with high water resistance for multiple applications - Chenning Sun; Kangkang Wang; Fu Wang; Xiaoxin Zhao; Sha Bai; Binbin Su; Huidong Xie (Chemical Engineering Journal, 2026)

Two new compounds isolated from a sponge-derived fungus Diaporthe sp. ZYX-Z-582 - Jia-Le Chang; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Hai-Tao Li; Jiao-Cen Guo; Hao-Fu Dai; Sha-Sha Liu; You-Xing Zhao (Phytochemistry Letters, 2026)

Covalently grafted pyrenoviologen on nano-SiO2 for ultrasensitive fluorescent detection of picric acid - Yiting Wang; Ni Yan; Yawen Li; Jiayao Sha; Yao Liu; Tianle Cao; Tianyue Yuan; Wenjie Ni; Weiqiao Wang; Jiuxu Fu; Gang He (Chemical Engineering Journal, 2026)

V-ATPase B mediates Bt Cry1Ac binding and toxicity in Grapholita molesta - Dandan Pan; Jiayang Feng; Jiacheng Ye; Xiaoyan Yang; Xiaoyan Zhang; Xiaofang Sha; Donghan Wang; Yanshen Fu; Chunxiao Men; Xiangqun Yuan; Yiping Li (Insect Biochemistry and Molecular Biology, 2025)

Genomic analysis of terpene synthase family and characterization of ent-kaurene synthase in Chenopodium quinoa - Shuaibing Tian; Liping Wang; Lijun Liu; Xiaoyu Sha; Jine Wu; Jingye Fu; Qiang Wang (Molecular Genetics and Genomics, 2025)

ATP synthase subunit γ mediates Cry1Ac binding and toxicity in Grapholita molesta - Jiayang Feng; Dandan Pan; Yichen Wang; Xiaoyan Zhang; Xiaofang Sha; Yanshen Fu; Jiacheng Ye; Donghan Wang; Xiangqun Yuan; Yiping Li (Pesticide Biochemistry and Physiology, 2025)

The protein kinase MLOP1 mediates pectin fragment signaling and feedback regulation of cell wall synthesis - Xiaohui Liu; Jingjing Sha; Qingyao Li; Shuai Yuan; Jialin Tao; Shihan Fu; Pu Gan; Qiuyan Lan; Johannes Liesche; Chaowen Xiao (Journal of Plant Physiology, 2025)

Middle Campanian to Maastrichtian foraminifera and biomarkers: Seawater incursion events in the Songliao Basin, Northeast China - Ke-Ying Yue; Sha Li; Tian Jiang; Dang-Peng Xi; Bo-Wen Song; Yu Liang; Li-Xin Sun; Tian-Fu Zhang; Hai-Chun Zhang; Xiao-Qiao Wan; Bo Wang (Palaeoworld, 2025)

A fish-gelatin-modified multifunctional hydrogel with “salt-in-water” for dendrite-free flexible zinc-ion batteries - Wen-Long Cheng; Zi-Qiang Cheng; Zi-Zi Hu; Ming-Ming Hu; Guang-Xian Liu; Lin-Feng Yuan; Yan-Hui Fu; Xiao-Mei Sha; Zong-Cai Tu (Chemical Engineering Journal, 2025)

DCNet: Full waveform inversion with difference convolution - Li-Sha Fu; Chang-Yang Hu; Leting Tan; Huawei Liao; Qiang Zhang; Fan Min (Journal of Applied Geophysics, 2025)

Study on the functional role and tissue localization of GmolTrypsin in larvae of Grapholita molesta feeding on different host plants - Dongbiao Lü; Dandan Pan; Donghan Wang; Jiacheng Ye; Xiaofang Sha; Xiaoyan Zhang; Yanshen Fu; Xiangqun Yuan; Yiping Li (Insect Biochemistry and Molecular Biology, 2025)

Hepatotoxic effects of exposure to different concentrations of Dibutyl phthalate (DBP) in Schizothorax prenanti: Insights from a multi-omics analysis - Luo Lei; Wuga Sha; Qing Liu; Shidong Liu; Yinhua Zhou; Rundong Li; Yuting Duan; Suxing Fu; Hejiao Li; Rongrong Liao; Linzhen Li; Rongzhu Zhou; et al. (Aquatic Toxicology, 2025)

Real-traffic emissions of CO, NOx, CO2, and PM2.5 from vehicles using a portable emission measurement system - Chunying Lu; Shuwei Dong; Shanqian Huang; Shuohan Gao; Jinsheng Fu; Xinyi Tian; Sha Lin; Xinzhu Xiong; Xinjun Wang; Xinfeng Wang (Air Quality, Atmosphere & Health, 2025)

Rapid degradation of frozen soil environments in thermokarst-affected alpine grasslands on the Qinghai-Tibet Plateau under climate change - Yuanhong Deng; Xiaoyan Li; Chao Yang; Fangzhong Shi; Shaojie Zhao; Sha Zhou; Chiyuan Miao; Ruiqiang Ding; Yongshuo H. Fu; Xiaofan Yang; Zhigang Wang (CATENA, 2025)

Dissipation of Ulva prolifera green tides across various spatial and temporal scales and the short-term effects on marine environments - Jiacheng Sun; Ke Liu; Haibo Zhang; Jie Fu; Xiaoyong Shi; Ziwei Yao; Gang Zhao; Zhenxia Sha; Hao Cui; Jinpeng Wu (Marine Environmental Research, 2025)

Achieving efficient phosphorescence of carbon dots via a synergistic enhancement strategy for bright field anti-counterfeiting - Jing Tan; Daiqi Yang; Chunyi Lu; Yi Li; Xingyu Gu; Peng Sha; Songnan Qu; Xin Wang; Lipei Fu; Qijun Li (Chemical Engineering Journal, 2025)

Combined skin injury model from airblast overpressure and seawater immersion in rats: establishment, characterization, and mechanistic insights - Jinpeng Du; Zhao Li; Yi Kong; Wei Song; Zhongming Chen; Mengde Zhang; Yuyan Huang; Chao Zhang; Xu Guo; Linhao Hou; Yaxin Tan; Liting Liang; et al. (Journal of Molecular Histology, 2025)

Kiwifruit polyphenols regulate mitophagy to promote intestinal barrier function: Based on proteomics, in vitro and in vivo study - Ruiyu Xu; Yan Zhou; Hongyan Niu; Sha Xue; Lijun Fu; Qun Huang; Yong Sun (Food Bioscience, 2025)

Entropy driven-based catalytic biosensors for bioanalysis: From construction to application-A review - Sha Yang; Xinyu Zhan; Lijia Yuan; Marc Lamy de la Chapelle; Weiling Fu; Xiang Yang (Analytica Chimica Acta, 2025)

PBAT biodegradable microplastics enhanced organic matter decomposition capacity and CO2 emission in soils with and without straw residue - Sha Chang; Chao Chen; Qing-Long Fu; Aoyu Zhou; Zhuyao Hua; Fengxiao Zhu; Shiyin Li; Huan He (Journal of Hazardous Materials, 2024)

Understory plant diversity supports the delivery of ecosystem multifunctionality on the Loess Plateau: A comparative of plantations and natural forests - Guoliang Sha; Huan Yu; Yuxuan Chen; Kang Ren; Pengcheng Xin; Xin Guo; Jing Xiao; Yanchao Fu (Journal of Environmental Management, 2024)

A viscoelastic wave propagation approach for dynamic backcalculation of layer properties of asphalt pavements under an impact load - Guozhi Fu; Dandan Cao; Ghim Ping Ong; Jiaqing Wang; Dong Sha (Computers and Geotechnics, 2024)

The resistance mechanism of humic acids and proteins in soluble microbial products from activated sludge against silver nanoparticles - Jia Kang; Yi-hang Wang; Yao-wen Zhang; Chu-qiong Song; Ao-di Wang; Ning Zhou; Yi-hui Zhang; Fa-zhan Li; Shu-li Liu; Li-sha Liu; Gang-fu Song; Bai-hong Wang (Journal of Environmental Chemical Engineering, 2024)

High dimensional proteomic mapping of bone marrow immune characteristics in immune thrombocytopenia - Feng-Qi Liu; Qing-Yuan Qu; Ying Lei; Qi Chen; Yu-Xiu Chen; Meng-Lin Li; Xue-Yan Sun; Ye-Jun Wu; Qiu-Sha Huang; Hai-Xia Fu; Yuan Kong; Yue-Ying Li; et al. (Science China Life Sciences, 2024)

The effect of quorum sensing on cadmium- and lead-containing wastewater treatment using activated sludge: Removal efficiency, enzyme activity, and microbial community - Taotao Zeng; Liangqin Wang; Xiaoya Ren; Naif Abdullah Al-Dhabi; Haichao Sha; Yusong Fu; Wangwang Tang; Jie Zhang (Environmental Research, 2024)

Improved physicochemical stability of fish oil nanoemulsion via a dense interfacial layer formed by hyaluronic acid-poly(glyceryl)10-stearate - Sha Ao; Xiang Luo; Hongze Wu; Yanyan Zhou; Qun Yang; Xuguang Yin; Hongliang Fu; Mengyu Huang; Dandan Lu; Kewu Zhu (Food Chemistry, 2024)

Draconibacterium aestuarii sp.nov., a Glycolipid-Producing Bacterium Isolated from Tidal Flat Sediment and Emended Description of the Genus Draconibacterium - Jia-Yan Wang; Sha-Sha Qiu; Yue Su; Wei-Yu Pan; Tao Wang; Wen-Wu Zhang; Ge-Yi Fu; Min Wu (Current Microbiology, 2024)

LIPUS regulates the progression of knee osteoarthritis in mice through primary cilia-mediated TRPV4 channels - Sha Wu; Haiqi Zhou; Huixian Ling; Yuyan Sun; Ziyu Luo; ThaiNamanh Ngo; Yuanyuan Fu; Wen Wang; Ying Kong (Apoptosis, 2024)
Osteoarthritis (OA) is a common disease in middle-aged and elderly people. An imbalance in calcium ion homeostasis will contribute to chondrocyte apoptosis and ultimately lead to the progression of OA. Transient receptor potential channel 4 (TRPV4) is involved in the regulation of intracellular calcium homeostasis. TRPV4 is expressed in primary cilia, which can sense mechanical stimuli from outside the cell, and its abnormal expression is closely related to the development of OA. Low-intensity pulsed ultrasound (LIPUS) can alleviate chondrocyte apoptosis while the exact mechanism is unclear. In this project, with the aim of revealing the mechanism of action of LIPUS, we proposed to use OA chondrocytes and animal models, LIPUS intervention, inhibition of primary cilia, use TRPV4 inhibitors or TRPV4 agonist, and use Immunofluorescence (IF), Immunohistochemistry (IHC), Western Blot (WB), Quantitative Real-time PCR (QP) to detect the expression of cartilage synthetic matrix and endoplasmic reticulum stress markers. The results revealed that LIPUS altered primary cilia expression, promoted synthetic matrix metabolism in articular chondrocytes and was associated with primary cilia. In addition, LIPUS exerted a active effect on OA by activating TRPV4, inducing calcium inward flow, and facilitating the entry of NF-κB into the nucleus to regulate synthetic matrix gene transcription. Inhibition of TRPV4 altered primary cilia expression in response to LIPUS stimulation, and knockdown of primary cilia similarly inhibited TRPV4 function. These results suggest that LIPUS mediates TRPV4 channels through primary cilia to regulate the process of knee osteoarthritis in mice.

Advancements in the loop-mediated isothermal amplification technique for the rapid detection of plant viruses in various crops - Ruizuo Fu; Yu Sha; Xiangbin Xu; Song-Bai Liu (Physiological and Molecular Plant Pathology, 2024)

Effects of biochar layer position on treatment performance and microbial community in subsurface flow constructed wetlands for removal of cadmium and lead - Haichao Sha; Xin Song; Naif Abdullah Al-Dhabi; Taotao Zeng; Yuemei Mao; Yusong Fu; Zheng Liu; Guohua Wang; Wangwang Tang (Bioresource Technology, 2024)

Correction to: Clinical Significance and Influencing Factors of Microvascular Tissue Reperfusion After Macrovascular Recanalization - Xuesong Bai; Fan Yu; Qiuyue Tian; Wei Li; Arman Sha; Wenbo Cao; Yao Feng; Bin Yang; Yanfei Chen; Peng Gao; Yabing Wang; Jian Chen; et al. (Translational Stroke Research, 2023)

Short-chain fatty acids facilitated long-term dechlorination of PCBs in Taihu Lake sediment microcosms: Evidence from PCB congener and microbial community analyses - Lei Xu; Yanqiang Tang; Sha Liu; Xi Chen; Ying Wang; Zheming Liu; Qingdong Qin; Dafang Fu; Yan Xu (Chemosphere, 2023)

Analytical solutions for contaminant transport through a GMB/CCL composite liner system considering effective porosity and thermodiffusion - Jin-Wei Qiu; Lu-Sha Jiang; He-Fu Pu; Ding-Bao Song; Ming Min; Jun Tong (Computers and Geotechnics, 2023)

Understanding how microbial electrolysis cell assisted anaerobic digestion enhances triclocarban dechlorination in sludge - Sha Long; Qizi Fu; Zhixiang Hao; Luyang Sun; Zihan Li; Yike Guo; Xuran Liu; Fengming Song; Dongbo Wang; Wenming Wang (Chemical Engineering Journal, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Two new bibenzyls from Pleione grandiflora (Rolfe) Rolfe and their antioxidant activity - Wei Li; Jia-Rui Fu; Li-Jun Zheng; Lin Ni; Jun-Qing Liu; Jun-Wen Zhai; Zhuang Zhou; Sha-Sha Wu (Natural Product Research, 2023)

Clinical Significance and Influencing Factors of Microvascular Tissue Reperfusion After Macrovascular Recanalization - Xuesong Bai; Fan Yu; Qiuyue Tian; Wei Li; Araman Sha; Wenbo Cao; Yao Feng; Bin Yang; Yanfei Chen; Peng Gao; Yabing Wang; Jian Chen; et al. (Translational Stroke Research, 2023)

Evaluation the role of soluble microbial products for denitrification sludge characteristic under starvation stress - Qian-Qian Zhang; Yan Yu; Jin-Ze Liu; Wen-Jing Fu; Jin-Yang Quan; Ying Chen; Jian-Qiang Zhao; Sha Wang; Ren-Cun Jin (Science of The Total Environment, 2023)

Late Eocene stepwise seawater retreat from the Pamir-Tian Shan convergence zone (Alay Valley) in the western Tarim Basin, China - Jimin Sun; Jingeng Sha; Brian F. Windley; Zhiliang Zhang; Bihong Fu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Soil moisture determines the recovery time of ecosystems from drought - Ying Yao; Yanxu Liu; Sha Zhou; Jiaxi Song; Bojie Fu (Global Change Biology, 2023)
Recovery time, the time it takes for ecosystems to return to normal states after experiencing droughts, is critical for assessing the response of ecosystems to droughts; however, the spatial dominant factors determining recovery time are poorly understood. We identify the global patterns of terrestrial ecosystem recovery time based on remote sensed vegetation indices, analyse the affecting factors of recovery time using random forest regression model, and determine the spatial distribution of the dominant factors of recovery time based on partial correlation. The results show that the global average recovery time is approximately 3.3 months, and that the longest recovery time occurs in mid‐latitude drylands. Analysis of affecting factors of recovery time suggests that the most important environmental factor affecting recovery time is soil moisture during the recovery period, followed by temperature and vapour pressure deficit (VPD). Recovery time shortens with increasing soil moisture and prolongs with increasing VPD; however, the response of recovery time to temperature is nonmonotonic, with colder or hotter temperatures leading to longer recovery time. Soil moisture dominates the drought recovery time over 58.4% of the assessed land area, mostly in the mid‐latitudes. The concern is that soil moisture is projected to decline in more than 65% regions in the future, which will lengthen the drought recovery time and exacerbate drought impacts on terrestrial ecosystems, especially in southwestern United States, the Mediterranean region and southern Africa. Our research provides methodological insights for quantifying recovery time and spatially identifies dominant factors of recovery time, improving our understanding of ecosystem response to drought.

Revealing an unrecognized role of free ammonia in sulfur transformation during sludge anaerobic treatment - Qizi Fu; Sha Long; Yunhao Xu; Yan Wang; Bentao Yang; Dandan He; Xuemei Li; Xuran Liu; Qi Lu; Dongbo Wang (Journal of Hazardous Materials, 2023)

Superior triethylamine sensing platform based on MOF activated by carbon dots for photoelectric dual-mode in biphasic system - Xue-Chun Yang; Sha-Qi Fu; Qian-Li Li; Zheng Jiao; Jing-Tai Zhao; Yun Guo; Zhi-Jun Zhang; Song Gao; Ling-Li Cheng (Chemical Engineering Journal, 2023)

Di-(2-ethylhexyl) phthalate impairs angiogenesis and hematopoiesis via suppressing VEGF signaling in zebrafish - Yang-Xi Hu; Bo-Wen Hu; Ya-Sha Chen; Hong-Min You; Mei-Rong Bai; Lu-Jun Zhang; Zhi-Fu Guo; Chun Liang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

[Cuproptosis-related immune gene signature predicts clinical benefits from anti-PD-1/PD-L1 therapy in non-small-cell lung cancer - Linfeng Luo; Anlin Li; Sha Fu; Wei Du; Li-Na He; Xuanye Zhang; Yixing Wang; Yixin Zhou; Yang Yunpeng; Zhang Li; Shaodong Hong (Immunologic Research, 2023)

Sourdough yeast-bacteria interactions results in reduced immunogenicity by increasing depolymerization and hydrolysis of gluten - Wenhui Fu; Xin Jia; Chenglong Liu; Xiao Meng; Ke Zhang; Sha Tao; Wentong Xue (Innovative Food Science & Emerging Technologies, 2023)

Global assessment of nature’s contributions to people - Yanxu Liu; Bojie Fu; Shuai Wang; Jonathan R. Rhodes; Yan Li; Wenwu Zhao; Changjia Li; Sha Zhou; Chenxu Wang (Science Bulletin, 2023)

Effect of phenol formaldehyde-associated microplastics on soil microbial community, assembly, and functioning - Hu Li; Qiu-Ping Luo; Sha Zhao; Yan-Yan Zhou; Fu-Yi Huang; Xiao-Ru Yang; Jian-Qiang Su (Journal of Hazardous Materials, 2023)

A comprehensive review on coupled processes and mechanisms of soil-vegetation-hydrology, and recent research advances - Zhongkai Li; Xiaoyan Li; Sha Zhou; Xiaofan Yang; Yongshuo Fu; Chiyuan Miao; Shuai Wang; Guanghui Zhang; Xiuchen Wu; Chao Yang; Yuanhong Deng (Science China Earth Sciences, 2022)

Notch1 down-regulation in lineage-restricted niches is involved in the development of mouse eccrine sweat glands - Yuzhen Wang; Bin Yao; Xianlan Duan; Jianjun Li; Wei Song; Enhejirigala; Zhao Li; Xingyu Yuan; Yi Kong; Yijie Zhang; Xiaobing Fu; Sha Huang (Journal of Molecular Histology, 2022)

Biogeography of culturable marine bacteria from both poles reveals that ‘everything is not everywhere’ at the genomic level - Qi‐Long Qin; Zhi‐Bin Wang; Qian‐Qian Cha; Sha‐Sha Liu; Xue‐Bing Ren; Hui‐Hui Fu; Mei‐Ling Sun; Dian‐Li Zhao; Andrew McMinn; Yin Chen; Xiu‐Lan Chen; Yu‐Zhong Zhang; et al. (Environmental Microbiology, 2022)
Summary Based on 16S rRNA gene analyses, the same bacterial operational taxonomic units (OTUs) are common to both the Arctic and Antarctic oceans, supporting the concept ‘everything is everywhere’. However, whether the same OTUs from both poles have identical genomes, i.e. whether ‘everything is still everywhere’ at the genomic level has not yet been examined systematically. Here, we isolated, sequenced and compared the genomes of 45 culturable marine bacteria belonging to three genera of Salinibacterium , Psychrobacter and Pseudoalteromonas from both polar oceans. The bacterial strains with identical 16S rRNA genes were common to both poles in every genus, and four identical genomes were detected in the genus Salinibacterium from the Arctic region. However, no identical genomes were observed from opposite poles in this study. Our data, therefore, suggest that ‘everything is not everywhere’ at the genomic level. The divergence time between bacteria is hypothesized to exert a strong impact on the bacterial biogeography at the genomic level. The geographical isolation between poles was observed for recently diverged, highly similar genomes, but not for moderately similar genomes. This study thus improves our understanding of the factors affecting the genomic‐level biogeography of marine microorganisms isolated from distant locations.

Magnetic Resonance Imaging-Guided and Navigated Individualized Repetitive Transcranial Magnetic Stimulation for Cognitive Impairment in Schizophrenia - Xu-Sha Wu; Tian-Cai Yan; Xian-Yang Wang; Yang Cao; Xiao-Fan Liu; Yu-Fei Fu; Lin Wu; Yin-Chuan Jin; Hong Yin; Long-Biao Cui (Neuroscience Bulletin, 2021)

Descending Modulation of Spinal Itch Transmission by Primary Somatosensory Cortex - Zi-Han Wu; Han-Yu Shao; Yuan-Yuan Fu; Xiao-Bo Wu; De-Li Cao; Sheng-Xiang Yan; Wei-Lin Sha; Yong-Jing Gao; Zhi-Jun Zhang (Neuroscience Bulletin, 2021)

Short-term effects of ambient temperature on preterm birth: a time-series analysis in Xuzhou, China - Peng Cheng; Lei Peng; Jingwen Hao; Sha Li; Chao Zhang; Lianjie Dou; Weinan Fu; Fan Yang; Jiahu Hao (Environmental Science and Pollution Research, 2021)

Insight into cellular dedifferentiation in regenerative medicine - Tian Hu; Bin Yao; Sha Huang; Xiaobing Fu (Science China Life Sciences, 2020)

Identifying common genome-wide risk genes for major psychiatric traits - Sha Liu; Shuquan Rao; Yong Xu; Jun Li; Hailiang Huang; Xu Zhang; Hui Fu; Qiang Wang; Hongbao Cao; Ancha Baranova; Chunhui Jin; Fuquan Zhang (Human Genetics, 2020)

An Integrated Decision Support Framework for Incorporating Fairness and Stability Concerns into River Water Allocation - Jianan Qin; Xiang Fu; Shaoming Peng; Sha Huang (Water Resources Management, 2020)

TNF-α suppresses sweat gland differentiation of MSCs by reducing FTO-mediated m6A-demethylation of Nanog mRNA - Yihui Wang; Rui Wang; Bin Yao; Tian Hu; Zhao Li; Yufan Liu; Xiaoli Cui; Liuhanghang Cheng; Wei Song; Sha Huang; Xiaobing Fu (Science China Life Sciences, 2020)

Synthesis and biological evaluation of novel disulfides incorporating 1,3,4-thiadiazole scaffold as promising antitumor agents - Sha Li; Hai-Xin Wang; Hai-Ying Liu; Fen Jing; Xiao-Yun Fu; Cai-Wen Li; Yan-Ping Shi; Bao-Quan Chen (Medicinal Chemistry Research, 2019)

The associations of air pollution exposure during pregnancy with fetal growth and anthropometric measurements at birth: a systematic review and meta-analysis - Li Fu; Yi Chen; Xinyi Yang; Zuyao Yang; Sha Liu; Lei Pei; Baixiang Feng; Ganxiang Cao; Xin Liu; Hualiang Lin; Xing Li; Yufeng Ye; et al. (Environmental Science and Pollution Research, 2019)

PM2.5 affects establishment of immune tolerance in newborn mice by reducing PD-L1 expression - Li Yan; Caihui Gong; Linyan Ying; Wenlong Fu; Sha Liu; Jihong Dai; Zhou Fu (Journal of Biosciences, 2019)

Photosynthetic acclimation of an evergreen broadleaved shrub (Ammopiptanthus mongolicus) to seasonal climate extremes on the Alxa Plateau, a cold desert ecosystem - Zhengzhen Li; Ximeng Li; Kennedy F. Rubert-Nason; Qiong Yang; Qiang Fu; Jinchao Feng; Sha Shi (Trees, 2018)

Characterization of the complete genome of euonymus yellow vein associated virus, a distinct member of the genus Potexvirus, family Alphaflexiviridae, isolated from Euonymus bungeanus Maxim in Liaoning, Northern China - Caixia Yang; Tong Han; Jingjing Fu; Yiming Liao; Sha Chen (Archives of Virology, 2018)

Effects of dietary fresh fermented soybean meal on growth performance, ammonia and particulate matter emissions, and nitrogen excretion in nursery piglets - Sai-sai Cheng; Yuan Li; Shi-jie Geng; Luan-sha Hu; Xiong-feng Fu; Xin-yan Han (Journal of Zhejiang University-SCIENCE B, 2017)

Anti-glomerular basement membrane glomerulonephritis with thrombotic microangiopathy: a case report - Xiao-juan Yu; Sha-sha Han; Su-xia Wang; Xiao-yu Jia; Wei-yi Guo; Zhao Cui; Feng Yu; Fu-de Zhou; Ming-hui Zhao (Immunologic Research, 2017)

Dynamic behaviour of the CO2 bubble in a bubble column bioreactor for microalgal cultivation - Yu-Dong Ding; Sha Zhao; Xun Zhu; Qiang Liao; Qian Fu; Yun Huang (Clean Technologies and Environmental Policy, 2016)

Effect of tidal stress on fault nucleation and failure of the 2007 M s6.4 Ning’er earthquake - ChaoDi Xie; XingLin Lei; XiaoPing Wu; Hong Fu; ZiYao Xiong; XiongLin Hu; Sha Li (Science China Earth Sciences, 2016)

The response and detoxification strategies of three freshwater phytoplankton species, Aphanizomenon flos-aquae, Pediastrum simplex, and Synedra acus, to cadmium - Xiaofei Ran; Hong Yue; Xiaoli Fu; Yuanhao Kang; Sha Xu; Yanjun Yang; Jinzhu Xu; Junqiong Shi; Zhongxing Wu (Environmental Science and Pollution Research, 2015)

The challenges of the post-COP21 regime: interpreting CBDR in the INDC context - Zou Ji; Fu Sha (International Environmental Agreements: Politics, Law and Economics, 2015)

Stem cell therapies and regenerative medicine in China - Sha Huang; XiaoBing Fu (Science China Life Sciences, 2014)

Bioaccumulation, subcellular, and molecular localization and damage to physiology and ultrastructure in Nymphoides peltata (Gmel.) O. Kuntze exposed to yttrium - Yongyang Fu; Feifei Li; Ting Xu; Sanjuan Cai; Weiyue Chu; Han Qiu; Sha Sha; Guangyu Cheng; Qinsong Xu (Environmental Science and Pollution Research, 2014)

Copper ultrastructural localization, subcellular distribution, and phytotoxicity in Hydrilla verticillata (L.f.) Royle - Qinsong Xu; Han Qiu; Weiyue Chu; Yongyang Fu; Sanjuan Cai; Haili Min; Sha Sha (Environmental Science and Pollution Research, 2013)

Dissimilar characteristics of umbilical cord mesenchymal stem cells from donors of different ages - Sha Huang; Changjiang Feng; Yan Wu; Siming Yang; Kui Ma; Xu Wu; Xiaobing Fu (Cell and Tissue Banking, 2013)

Variations of pore water sulfate gradients in sediments as indicator for underlying gas hydrate in Shenhu Area, the South China Sea - LuShan Wu; ShengXiong Yang; JinQiang Liang; Xin Su; ShaoYing Fu; ZhiBin Sha; Tao Yang (Science China Earth Sciences, 2013)

Molecular Cloning and Characterization of Two 9-Lipoxygenase Genes from Taxus chinensis - Shu-tao Li; Meng Zhang; Chun-hua Fu; Sha Xie; Yu Zhang; Long-jiang Yu (Plant Molecular Biology Reporter, 2012)

Laboratory assessment of uptake and toxicity of lanthanum (La) in the leaves of Hydrocharis dubia (Bl.) Backer - Qinsong Xu; Yongyang Fu; Haili Min; Sanjuan Cai; Sha Sha; Guangyu Cheng (Environmental Science and Pollution Research, 2012)

Enhancing Taxol Biosynthesis by Overexpressing a 9-Cis-Epoxycarotenoid Dioxygenase Gene in Transgenic Cell Lines of Taxus chinensis - Shu-tao Li; Chun-hua Fu; Meng Zhang; Yu Zhang; Sha Xie; Long-jiang Yu (Plant Molecular Biology Reporter, 2012)

Late Triassic bivalves associated with a hydrothermal vent system in the Yidun Island Arc (SW China) of the eastern Tethys - Li Lin; LiDong Zhu; YanChun Pang; JinGeng Sha; Franz T. Fürsich; XiuGen Fu; XinLi Wang (Science China Earth Sciences, 2011)

Cloud variations under subtropical high conditions - Sha Feng; Qi Liu; Yun-Fei Fu (Advances in Atmospheric Sciences, 2011)

Differential Expression of Serine/Threonine Protein Phosphatase Type-2C Under Drought Stress in Maize - Fu-Hua Li; Feng-Ling Fu; Li-Na Sha; Liang He; Wan-Chen Li (Plant Molecular Biology Reporter, 2009)

Inhibition on Hepatitis B virus in vitro of recombinant MAP30 from bitter melon - Jian Ming Fan; Qiao Zhang; Jun Xu; Sha Zhu; Tao Ke; De Fu Gao; Yu Bao Xu (Molecular Biology Reports, 2009)

Small heat-shock protein 22 mutated in autosomal dominant Charcot-Marie-Tooth disease type 2L - Bei-sha Tang; Guo-hua Zhao; Wei Luo; Kun Xia; Fang Cai; Qian Pan; Ru-xu Zhang; Fu-feng Zhang; Xiao-min Liu; Biao Chen; Cheng Zhang; Lu Shen; et al. (Human Genetics, 2005)